Bead milling for lipid recovery from thraustochytrid cells and selective hydrolysis of Schizochytrium DT3 oil using lipase. (January 2016) - Byreddy, Avinesh R.; Barrow, Colin J.; Puri, Munish
Highlights: Bead mill can be used as cell disruption technique for lipid extraction from thraustochytrids. Less energy was consumed for cell disruption compared with other methods. Maximum lipid recovery was achieved in 4 min processing time. Lipase concentration resulted in an 88.7% increase in omega-3 fatty acid. Abstract: Marine microalgae present a renewable alternative source for sustainable production of omega-3 fatty acids, as compared to conventional sources such as krill oil and fish oil. In this study, we optimised a method for lipid extraction from marine thraustochytrids using a bead mill and enzymatic concentration of omega-3 fatty acids from the thraustochytrid oil. The optimised lipid extraction conditions were, bead size 0.4–0.6 μm, 4500 rpm, 4 min of processing time at 5 g biomass concentration. The maximum lipid yield (% dry weight basis) achieved at optimum conditions were 40.5% for Schizochytrium sp. S31 (ATCC) and 49.4% for Schizochytrium sp. DT3 (in-house isolate). DT3 oil contained 39.8% docosahexaenoic acid (DHA) as a percentage of lipid, a higher DHA percentage than S31. Partial hydrolysis of DT3 oil using Candida rugosa lipase was performed to enrich omega-3 polyunsaturated fatty acids (PUFAs) in the glyceride portion. Total omega-3 fatty acid content was increased to 88.7%.